FORMULATION AND EVALUATION OF BUCCOADHESIVE TABLETS OF BUSPIRONE HYDROCHLORIC ACID - RAVAL, JIGNYASA; YAGNIK, ANKITA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The aim of the study was to prepare and evaluate buccal-adhesive tablets of buspirone hydrochloric acid (HCl) that avoids gastric degradation and first-pass metabolism, thereby increasing the drug bioavailability and onset of action. Buspirone HCl belongs to a class anxiolytic agent and a serotonin receptor agonist belonging to the azaspirodecanedione class of compounds. Methods: In the present work, different ratios of Gantrez MS 955 along with Carbopol 934 were studied to give bioadhesive strength. A 32 full factorial design was applied to investigate the combined effect of Gantrez MS 955 concentration (X1) and Carbopol 934 concentration (X2). Results: Results of the multiple regression analysis revealed that the independent variables significantly affected the dependent variables (bioadhesive strength [Y1], Q2 [Y2], Q3 [Y3], Q4 [Y4]). On the basis of multiple linear regression analysis and contour plot evaluation, it was found that the combination of two polymers possessed excellent mucoadhesive properties allowing ease of application and removal of the tablets from the buccal mucosa. Conclusion: The formulation batch A9 fulfilled all the criteria set from the desirability search. From the in vitro diffusion study, flux was calculated for the optimized batch. A study of the effect of tablet diameter and the environmental factors on the bioadhesion of the tablet was done. To study the environmental factor on bioadhesion, prehydration time and contact time were considered. Results found that increase in prehydration time decrease in bioadhesive strength and increase in contact time increased bioadhesive strength. Thus, a stable buccoadhesive formulation optimized for formulation ingredients and process parameters was prepared successfully.